RETRO-ORBITA EXTRAPLEURAL SOLITARY FIBROUS TUMOR - Mahastuti, Ni Made; Saputra, Herman; Gotra, I Made (Medicina; Vol 46 No 3 (2015): September 2015)
Extrapleural solitary fibrous tumor (SFT) merupakan tumor jaringan mesenkimal tipe fibroblastikdengan gambaran haemangipericytoma-like branching vascular yang menonjol dan sangat jarangdijumpai. Penderita perempuan usia 38 tahun mengeluh mata kanan menonjol sejak 2 tahun yanglalu.  Klinis ditemukan massa menonjol di belakang mata kanan. Pada pencitraan CT scan tampakmassa solid heterogen di cavum orbita kanan, tidak menginfiltrasi bulbus okuli. Makroskopis, massasolid berbatas tegas di regio retro orbita, berukuran 6,5 x 6,5 x 6 cm. Mikroskopis, tumor berbatastegas, sebagian besar tampak hiperselular mengandung proliferasi sel spindel neoplastik diselingidengan haemangipericytoma-like branching vascular yang menonjol. Mitosis sulit ditemukan. Pulasanimunohistokimia CD34 positif kuat dan Ki67 kurang dari 5%.  Pasien didiagnosis retro-orbitaextrapleural SFT  berdasarkan temuan klinis, radiologis, makroskopis, mikroskopis yang khas sertapemeriksaan imunohistokimia.  [MEDICINA 2015;46:195-200]. Extrapleural solitary fibrous tumor (SFT) is an ubiquitous mesenchymal tumour of fibroblastic type,which shows a prominent  haemangipericytoma-like branching vascular. A 38 years old woman camewith protruding right eye since 2 years ago. Clinical examination found a protruding mass in the rightretro orbita. Computed tomography scan demonstrated heterogen solid mass in right cavum orbitawithout infiltration into bulbus oculi. Macroscopically, the tumour appeared as well circumscribedsolid mass 6,5 x 6,5 x 6cm. Microscopic examination showed well circumscribed tumour, hypercellular,consist of neoplastic spindle cell proliferation intermingled with  prominent haemangiopericytomalikebranching vascular pattern . Mitoses are rarely found. CD34 stained strongly positive with lowexpressionof  Ki67 (< 5%). The diagnosis was made based on the clinical data, radiologic, histopathologicfindings,and also immunohistochemistry staining. [MEDICINA2015;46:195-200].
Keywords: extrapleural solitary fibrous tumor, retro orbita